2018
DOI: 10.1002/smll.201803101
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Synthesis of Iodinated Polypyrrole Nanoparticles for CT Imaging Guided Photothermal Therapy of Tumors

Abstract: Theranostic materials are of great significance to a personalized precise medicine. However, conventional theranostic agents are mainly fabricated by combining presynthesized independent imaging probes and therapeutic agents, suffering from multiple synthesis procedures, poor morphological control, and time/reagent‐consuming process. Herein, iodinated polypyrrole (I‐PPy) nanoparticles are fabricated via a one‐step synthesis strategy combining chemical oxidation and iodination for computed tomography (CT) imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 64 publications
0
41
0
Order By: Relevance
“…Various photothermal materials have been widely exploited as drug delivery carriers or coupling reagents for cancer therapy, including metal-organic frameworks and carbon dots [24][25][26][27]. Among these materials, conjugated polymer dots (Pdots) are biocompatible, degradable, and nontoxic biomaterial with easy functionalization.…”
Section: Near-infrared Light Absorption Hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…Various photothermal materials have been widely exploited as drug delivery carriers or coupling reagents for cancer therapy, including metal-organic frameworks and carbon dots [24][25][26][27]. Among these materials, conjugated polymer dots (Pdots) are biocompatible, degradable, and nontoxic biomaterial with easy functionalization.…”
Section: Near-infrared Light Absorption Hydrogelmentioning
confidence: 99%
“…Iohexol is an efficient and safe contrast agent approved by U.S. Food and Drug Administration for body computed tomography (CT) imaging [ 35 ]. However, the time of Iohexol for CT imaging is very short, and this inevitable shortcoming limits Iohexol widely used in the clinic [ 26 ]. Grating iohexol into Pdots-DOX-based thermosensitive hydrogel can successfully overcome this disadvantage of iohexol for enhanced CT imaging ability.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used contrast agent for CT is iodine‐containing organic molecules. Zou et al [11] prepared iodinated polypyrrole (I‐PPy) by chemical oxidation combined and iodination. CT imaging of I‐PPy revealed that CT value presented a linearly increasing trend with the concentration of I‐PPy solution.…”
Section: Single‐mode Imagingmentioning
confidence: 99%
“…[ 19 , 20 ] and organic materials (polydopamine nanoparticle, polypyrrole nanoparticle, etc.) [ 21 , 22 ], the scattered light interference, nonuniform heat distribution of the edges and low energy penetration into the deep tissue make them insufficient effect to completely eradicate tumor tissue, resulting in the incomplete tumor ablation and tumor recurrence [ 23 ].…”
Section: Introductionmentioning
confidence: 99%